TINJAUAN PUSTAKA SISTEMATIS: PENERAPAN METODE OPAC (ONLINE PUBLIC ACCESS CATALOGUE) PADA SISTEM TEMU BALIK INFORMASI - Afridar, Halim; Nurul Fadilah; Aang Alim Murtopo (Jurnal Publikasi Teknik Informatika, 2022)
Information retrieval system is a study in obtaining information in a document. One of the methods applied to the information retrieval system is the OPAC (Online Public Access Catalog) procedure. This study aims to determine the application of the OPAC (Online Public Access Catalog) method to the information retrieval system. The research procedure used is a library research procedure with a qualitative approach. Meaning that researchers get data by analyzing, organizing, sources derived from articles, books, reports, and other sources. The results show that the development of information systems brings changes to all aspects of human life, including libraries. Libraries are starting to become increasingly sophisticated. implemented in their services, the library service has started using OPAC as a form of applying the OPAC method to the information retrieval system, the systematic literature review method was applied in this study to analyze and identify previous studies related to this topic.